(untitled) (Research, Society and Development, 2022)
Introduction: Infectious diseases are frequent challenges for public health worldwide, the pandemic COVID-19 has provoked the use of remote technologies in teaching and has changed the way of educating. Objectives: Evaluate the perception of medical students regarding remote learning during social isolation, identify their main difficulties and compare performance with classroom teaching. Methods: Public opinion field research, with a descriptive quantitative approach and cross-sectional design. Results: The average ranking is 3.10 at the classroom teaching and 1.43 at the remote learning demonstrates a difficulty for students to follow an organized routine at the remote learning. When asked about the focus during classes, the classroom teaching modality obtained an average ranking of 2.21 and an remote learning of 1.85. Discussion: Focus and attendance of medical students in remote activities were compromised. The results showed a decrease in the taste for classes and exhaustion with the remote learning. Conclusion: There was a decrease at the performance in relation to classroom teaching, tiredness, difficulty in organizing and increased anxiety.